Genome sequence of the Asian Tiger mosquito,Aedes albopictus,reveals insights into its biology, genetics, and evolution - Chen, Xiao-Guang; Jiang, Xuanting; Gu, Jinbao; Xu, Meng; Wu, Yang; Deng, Yuhua; Zhang, Chi; Bonizzoni, Mariangela; Dermauw, Wannes; Vontas, John; Armbruster, Peter; Huang, Xin; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
The Asian tiger mosquito,Aedes albopictus,is a highly successful invasive species that transmits a number of human viral diseases, including dengue and Chikungunya fevers. This species has a large genome with significant population-based size variation. The complete genome sequence was determined for the Foshan strain, an established laboratory colony derived from wild mosquitoes from southeastern China, a region within the historical range of the origin of the species. The genome comprises 1,967 Mb, the largest mosquito genome sequenced to date, and its size results principally from an abundance of repetitive DNA classes. In addition, expansions of the numbers of members in gene families involved in insecticide-resistance mechanisms, diapause, sex determination, immunity, and olfaction also contribute to the larger size. Portions of integrated flavivirus-like genomes support a shared evolutionary history of association of these viruses with their vector. The large genome repertory may contribute to the adaptability and success ofAe. albopictusas an invasive species.